2019
DOI: 10.1097/md.0000000000015277
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of postprocedural anticoagulation after primary percutaneous coronary intervention for ST-segment elevation myocardial infarction

Abstract: There exists controversy on whether and for how long anticoagulation is necessary after primary percutaneous coronary intervention (PCI) for ST-segment elevation myocardial infarction (STEMI).We aimed to study the impact of prolonged (>24 h) or brief (<24 h) postprocedural anticoagulation on infarct size assessed by cardiac magnetic resonance (CMR) after 30 days as well as on left ventricular ejection fraction (LVEF) and left ventricular (LV) remodeling evaluated by 2D-echocardiography after 9 months from the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…The complications and quality of life cannot be effectively controlled, and the prognostic effect can be reduced. In order to reduce the damage to the myocardium, clinical treatment is often supplemented by western medicine [ 14 ], but the effect is not good.…”
Section: Discussionmentioning
confidence: 99%
“…The complications and quality of life cannot be effectively controlled, and the prognostic effect can be reduced. In order to reduce the damage to the myocardium, clinical treatment is often supplemented by western medicine [ 14 ], but the effect is not good.…”
Section: Discussionmentioning
confidence: 99%
“…These findings suggest that routine AC for PE prophylaxis is unlikely to provide benefit after a successful, uncomplicated PPCI procedure with early ambulation. Song et al [21] found a slight, though not statistically significant, decrease in infarct size by CMR in the prolonged anticoagulation group compared to the brief anticoagulation group at 30 days post-PPCI.…”
Section: Discussionmentioning
confidence: 92%
“…Currently, multiple therapy options, including thrombolytic drugs, percutaneous transluminal coronary angioplasty (PTCA), and coronary artery bypass grafting, are available to treat acute MI in clinic (Kahn et al, 1993;Sorensen and Maeng, 2015;Lhermusier et al, 2019;Song et al, 2019). In addition to medications and surgeries, epidemiological evidence has shown that exercise, such as stair climbing, walking, and sports, is inversely correlated to the mortality of cardiovascular causes (PaffenbargerJr., Hyde et al, 1986).…”
Section: Introductionmentioning
confidence: 99%